On the taxonomy of some South American and Australo-Pacific Anthicidae Latreille, 1819 (Coleoptera) with new subfamily and tribe-rank synonymies - Telnov, Dmitry (Zootaxa, 2024)
A monotypic South American genus Micreurygenius Pic, 1942 (hitherto in Eurygeniinae LeConte, 1862) is synonymized with Ischyropalpus La Ferté-Sénectère, 1849 (Anthicini Latreille, 1819) and, accordingly, moved to Anthicinae Latreille, 1819. A new combination is proposed for its only known species, Ischyropalpus angustatus (Pic, 1942) comb. nov., the species is herein tentatively attributed to the I. eryngii Werner, 1966 informal species-group. The Lemodinae Matthews, 1987 is synonymized with Copobaeninae Abdullah, 1969 and Copobaenus Fairmaire & Germain, 1863 is found congeneric with Trichananca Blanchard, 1891 syn. nov. based on adult morphology. New combinations are proposed for species hitherto attributed to Trichananca Blackburn, 1891: Copobaenus apterus (Lea, 1922) comb. nov., C. bicoloratus (Gemminger in Gemminger & Harold, 1870) comb. nov., C. cheesmanae (Telnov, 2019) comb. nov., C. concolor (King, 1869) comb. nov., C. frenchi (Pic, 1913) comb. nov., C. fulgidus (Werner & Chandler, 1995) comb. nov., C. hornabrooki (Uhmann, 1995) comb. nov., C. inexpectatus (Telnov & Degiovanni, 2021) comb. nov., C. marziae (Moore & Vidal, 2005) comb. nov., C. micromelas (Lea, 1922) comb. nov., C. neotropicus (Telnov & Degiovanni, 2021) comb. nov., C. nigripennis (Lea, 1917) comb. nov., C. novacaledonicus (Telnov, 2019) comb. nov., C. pisoniae (Lea, 1917) comb. nov., C. poggii (Telnov & Degiovanni, 2021) comb. nov., C. poqui (Guerrero & Diéguez, 2018) comb. nov., C. rugulosus (Uhmann, 2007) comb. nov., C. uniformis (Lea, 1922) comb. nov., C. valenciai (Moore & Vidal, 2005) comb. nov., C. victoriensis (Blackburn, 1891) comb. nov., C. vinctus (Erichson, 1842) comb. nov. Copobaenus erratus sp. nov. from Chile is described. The Eurygeniinae LeConte, 1862 tribe Ictistygnini Borchmann, 1936 is found contribal and is synonymized with Eurygeniini LeConte, 1862 based on adult morphology. An updated key to Eurygeniinae LeConte, 1862 tribes is presented. Setosicornia Pic, 1911, an obscure monotypic South American tenebrionoid genus, is redescribed and moved to the anthicid tribe Eurygeniini (Eurygeniinae) from Ripiphoridae Laporte 1840. A monotypic South American genus Atenizoides Gilmour, 1968, originally placed in Cerambycinae Audinet-Serville, 1832 (Cerambycidae Audinet-Serville, 1832), and placed in the Eurygeniini by Phillip and Ivie (1989), is found to be congeneric with Setosicornia and a new generic synonym is introduced. A new combination is proposed for its only known species, Setosicornia curacaoae (Gilmour, 1968) comb. nov., and this species is redescribed herein.